Respuesta :
Expression 6^–3 can be rewritten as:
1/6^3 = (1/6)^3
Therefore the answer is D
Hope that helps you
1/6^3 = (1/6)^3
Therefore the answer is D
Hope that helps you
Answer:
[tex]6^{-3}[/tex]
Step-by-step explanation:
Given : [tex]6^{-3}[/tex]
To Find: Which expression is equivalent to [tex]6^{-3}[/tex]
Solution:
Identity :[tex]x ^{-1}=\frac{1}{x}[/tex]
So, [tex]6^{-3}[/tex] = [tex](\frac{1}{6})^3[/tex]
[tex]6^{-3}[/tex] = [tex](\frac{1}{6})^3[/tex]
So, [tex](\frac{1}{6})^3[/tex] is equivalent to [tex]6^{-3}[/tex]
Thus Option D is correct.